2016
DOI: 10.4103/2141-9248.183944
|View full text |Cite
|
Sign up to set email alerts
|

Accidental childhood poisoning in Enugu, South-East, Nigeria

Abstract: Background:Accidental childhood poisoning is one of the recognized causes of morbidity and mortality in children under the age of 5 years worldwide. The prevalence and type of substance ingested vary from place to place and over time.Aim:This study was conducted with the aim of ascertaining the frequency and pattern of accidental childhood poisoning in Enugu.Subjects and Methods:This retrospective study was conducted at the Emergency Paediatric Unit of the University of Nigeria Teaching Hospital, Enugu, South-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 12 publications
9
27
3
7
Order By: Relevance
“…Also, the findings have shown that the majority of chemical poisoning cases occurred among Saudis, which is consist with other Saudi studies [ 30 , 31 ]. Besides, accidental chemical poisoning has been recorded in several studies consisting of the study findings [ 35 , 36 ]. Interestingly, the present study findings report that accomplished strongest bleach (chlorines) (Clorox®) was the commonest household products implicated in chemical poisoning, which is consistent with a study in Qatar and another study in Jeddah that highlighting a high incidence of chemical poising among children [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings have shown that the majority of chemical poisoning cases occurred among Saudis, which is consist with other Saudi studies [ 30 , 31 ]. Besides, accidental chemical poisoning has been recorded in several studies consisting of the study findings [ 35 , 36 ]. Interestingly, the present study findings report that accomplished strongest bleach (chlorines) (Clorox®) was the commonest household products implicated in chemical poisoning, which is consistent with a study in Qatar and another study in Jeddah that highlighting a high incidence of chemical poising among children [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…By 2002-2011, Benin City in the south-south area of Edo state reported higher cases of kerosene poisoning as well. Notwithstanding the fact that western cities of Lagos, Ilesha, Ile Ife and Ado Ekiti were epicenters of accidental childhood kerosene poisoning over the years, the victims were mostly from the lower socio-economic stratification in society [37][38][39][40]18]. From the emerging trends, spatial patterns, and the frequency of the hazards in the study area, opportunities are abound in the current study to undertake a risk assessment using a mix scale model targeting the affected states in Nigeria.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from this study show that household cleaning agents (liquid bleach, liquid soap, and detergent) were the most ingested chemical substance among under-five children in Calabar South LGA of Cross River State, this shows a shift from kerosene ingestion reported by Edelu et al [17] and Ugwu et al [39] The reasons for this shift are yet to be ascertained.…”
Section: Relationship Between Socioeconomic Status Of the Mother/caregiver And Risk Of Unintentional Ingestion Of Chemicals Among Under-fmentioning
confidence: 60%
“…Residential apartment also showed a strong statistical relationship (0.043 < P > 0.05) with risk of unintentional ingestion of chemical among under-five children, under-five children whose mothers/caregivers live in a one bedroom apartment, two bedroom apartments, and in communal apartment are 2 times more likely to experience unintentional ingestion of chemicals. This is not surprising because Edelu et al, [17] in their study done to ascertain the frequency and pattern of accidental childhood poisoning in Enugu, showed that the prevalence of unintentional childhood poisoning was higher among those with low socioeconomic background.…”
Section: Relationship Between Socioeconomic Status Of the Mother/caregiver And Risk Of Unintentional Ingestion Of Chemicals Among Under-fmentioning
confidence: 93%